Cover Image, Volume 139, Issue 38. Issue 38 (1st September 2022) - Elkihel, Abdechakour; Vernisse, Charlotte; Ouk, Tan‐Sothéa; Lucas, Romain; Chaleix, Vincent; Sol, Vincent
Abstract : This cover image by Vincent Sol and co‐authors shows the development of novel bio‐based hydrogels which are attractive materials for many biomedical purposes, such as drug delivery or wound healing. A light‐triggered antibacterial activity can be conferred to hydrogels after their conjugation to appropriate photosensitizers on xylan. The study of the morphology and rheology of the hydrogels showed that the materials obtained present interconnected porous structures and good mechanical integrities, as well as high swelling ratios. Photo‐bactericidal activity of these hydrogels have been showed under white light irradiation against Staphylococcus aureus and Pseudomonas aeruginosa . DOI: 10.1002/app.52744